LEGAL CERTAINTY OF ECONOMIC RIGHTS FOR UNREGISTERED CREATORS IN COLLECTIVE MANAGEMENT ORGANIZATIONS - Anak Agung Bagus Jaya Adri Putra; Nyoman Satyayudha Dananjaya (Transpublika Publisher, 2024)
This writing aims to analyze, identify, and elaborate on the legal protection of the economic rights of copyrighted works in Indonesia, based on the UUHC (Undang-Undang Hak Cipta or Copyright Law), and the legal certainty of economic rights for creators who are not registered with the Collective Management Institute after the enactment of PP (Peraturan Pemerintah or Government Regulation) Number 56 of 2021 concerning the Management of Copyright and/or Music Royalties. This study employs normative research with a statutory approach and analysis of legal concepts. The results indicate that the protection of creators' economic rights under the UUHC is regulated by Article 9, paragraph 3, which states that